Synthesis and Evaluation of Antimicrobial Activity of the Rearranged Abietane Prattinin A and Its Synthetic Derivatives - Mustapha Ait El Had; Manal Zefzoufi; Houda Zentar; Lahoucine Bahsis; Mouhi Eddine Hachim; Adib Ghaleb; Choukri Khelifa-Mahdjoubi; Hafida Bouamama; Ramón Alvarez-Manzaneda; José Justicia; Rachid Chahboun (Molecules, 2024)
Synthesis of the natural product prattinin A and some new derivatives has been achieved using abietic acid. The final products and a selection of intermediates were evaluated for their antibacterial activity against three human pathogenic bacteria: E. coli, P. aeruginosa, and S. aureus. The results showed that the antibacterial activity varies depending on the chemical structure of the compounds. Notably, compound 27 exhibited the most potent activity against E. coli and P. aeruginosa, with a minimal inhibitory concentration (MIC) of 11.7 µg/mL, comparable to that of the standard antibiotic ciprofloxacin, and strong activity against S. aureus, with an MIC of 23.4 µg/mL. Furthermore, we assessed the stability of these derivative compounds as potential antimicrobial agents and determined their interactions with the crystal structure of the protein receptor mutant TEM-12 from E. coli (pdb:1ESU) using molecular docking via UCSF Chimera software 1.17.3. The results suggest that 27 has potential as a natural antibiotic agent.